Critical thinking : developing the intellectual tools for social justice - Zornado, Joseph L.; Harrison, Jill, 1963-; Weisman, Daniel (Abingdon, Oxon ; New York, NY : Routledge, 2020)
"Critical Thinking presents, defines and explains the intellectual skills and habits of mind that comprise critical thinking and its relationship to social justice. Each of the sequential chapters includes detailed examples and learning exercises that guide the reader step by step from intellectual competency, to critical thinking, to cultural cognition, and to critical awareness necessary for social justice. The book documents and explains the scope of multiple crises facing society today, including environmental destruction, income and wealth inequality, large-scale human migration, and the rise of autocratic governments. It shows how critical thinking, cultural cognition, and critical awareness lead to the possibility of solutions grounded in social justice. All college students, especially those in the social sciences and humanities, will develop the intellectual skills necessary for critically engaging information in order to become active learners and effective agents in the world. This book complements information in introductory, interdisciplinary, or discipline-specific courses. Every chapter contains examples and exercises that can be assigned as homework, adopted as in-class activities, or both. The Conclusion also contains exercises for developing writing and basic mathematical competency skills"--
OCLC-licensed vendor bibliographic record.
Keywords: Social justice; Restorative justice; Critical thinking; SOCIAL SCIENCE / General; SOCIAL SCIENCE / Sociology / General